Mapping the integrity of rock mass with GPR: case study in decommissioning mining - Duz, Beatriz Guzzo [UNESP]; Moreira, César Augusto [UNESP]; Casagrande, Matheus Felipe Stanfoca [UNESP]; Helene, Livia Portes Innocenti (Springer Nature, 2023)
Abstract: Slopes are built for the purpose of extracting ore, in the case of mining, or access roads in civil works. The excavation of slopes in tropical countries is facilitated by the thick layer of soil formed from the more intense weathering when compared to other countries. However, the residence time of water in the soil is relatively longer and consequently allows the accumulation and percolation of water through rock fractures even in the dry period. These factors induce a greater probability of occurrence of ruptures. Mines in the decommissioning phase must guarantee slope stability conditions even after closure in order to comply with legislation and environmental safety. In this work, the slopes of a decommissioning mine were investigated using geophysical methods (GPR) and structural analysis of the rock mass. The results were presented in the form of radargrams that correlate distance and depth of investigation. Structural data served as the basis for the execution of kinematic analyzes for planar and wedge ruptures. The analysis of the results allowed the correlation between electromagnetic signal attenuation zones, with the presence of water and the occurrence of ruptures. Thus, the GPR results allowed the recognition of structural discontinuities, accumulation zones and water flow.
Keywords: Aquifer fractured; Civil work; Failures; Geophysics; Mining decommissioning